2001
DOI: 10.1161/01.cir.103.17.2176
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional Glenn Procedure Improves the Mechanical Efficiency of a Total Cavopulmonary Connection in High-Risk Fontan Candidates

Abstract: The volume reduction of BDG preceding TCPC allows for any afterload mismatch to be corrected, thereby improving ventricular energetics after TCPC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
90
1
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(101 citation statements)
references
References 28 publications
5
90
1
2
Order By: Relevance
“…by guest on May 12, 2018 http://circres.ahajournals.org/ Downloaded from are consistent with the fact that volume reduction by staged palliation could enhance ventricular contractility as well as mechanical efficiency, as shown by cardiac elastance measurement in this study. 22 Thus, the functional benefits of CDCs isolated from children in this study could be interpreted, at least in part, by previous reports on mouse and human demonstrating that the intrinsic pool of cardiac progenitor cells in human neonatal heart was found to have a higher capability to regenerate cardiomyocytes than that in adult myocardium. 6,7,39 The sample size of this exploratory trial was set as small, based on feasibility and the results of our preclinical trial, which could limit the statistical rigor and power and might not be sufficient to draw the preliminary conclusions related to safety and efficacy.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…by guest on May 12, 2018 http://circres.ahajournals.org/ Downloaded from are consistent with the fact that volume reduction by staged palliation could enhance ventricular contractility as well as mechanical efficiency, as shown by cardiac elastance measurement in this study. 22 Thus, the functional benefits of CDCs isolated from children in this study could be interpreted, at least in part, by previous reports on mouse and human demonstrating that the intrinsic pool of cardiac progenitor cells in human neonatal heart was found to have a higher capability to regenerate cardiomyocytes than that in adult myocardium. 6,7,39 The sample size of this exploratory trial was set as small, based on feasibility and the results of our preclinical trial, which could limit the statistical rigor and power and might not be sufficient to draw the preliminary conclusions related to safety and efficacy.…”
Section: Discussionsupporting
confidence: 51%
“…The approximations of E es (end-systolic elastance) and E a (effective arterial elastance) were calculated by pressure study and volume measurement, as previously reported. 22 cMRI scans were performed on a Philips 1.5 Tesla Achieva Scanner (Philips Healthcare, Netherlands) under general anesthesia. The phased array coil was selected.…”
Section: Cardiac Function Analysismentioning
confidence: 99%
“…This is probably because the resultant circulation with a cavopulmonary shunt is more stable than a circulation in parallel, such as with the Norwood procedure, and ventricular function has been shown to be better after a volume unloading procedure [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…Die Vorteile bestehen darin, dass die Probleme einer pulmonalen Drucksteigerung und einer Volumenüberlastung des einzig verfügbaren Pumpventrikels deutlich reduziert und damit Anzahl und Schweregrad der einzelnen Risikofaktoren gesenkt werden konnten [37,76]. In einem zweiten Schritt erwartet diese Kinder nach 6-12 Monaten dann die komplette Fontanisierung mit deutlich verringertem Operationsrisiko.…”
Section: Choussat-kriterienunclassified
“…Eine verbesserte Patientenselektion während der letzten Dekade und die günstigere Wahl von Zeitpunkt und Art der einzelnen Operationsschritte führten zu einer Reduktion ungünstiger Prognosefaktoren, welche wesentlich durch die über längere Zeiträume bestehende Volumenüberlastung des Pumpventrikels bedingt wurden [50,63,74,76]. Bei den postoperativen Verlaufskontrollen nach Fontan-Prozedur fühlen sich die meisten Kinder, unabhängig davon, ob der Tunnel intraoder extrakardial verlegt worden ist, subjektiv wohl.…”
Section: Belastbarkeit Nach Fontan-operationunclassified